A manganese(I) complex with a 190 ns metal-to-ligand charge transfer lifetime - Sandra Kronenberger; Robert Naumann; Christoph Förster; Nathan R. East; Jan Klett; Katja Heinze (Nature Communications)
Abstract Application of photoactive transition metal complexes in lighting, imaging, sensing, and photocatalysis is usually based on the triplet metal-to-ligand charge transfer (3MLCT) excited state of precious metal complexes with 4/5d6 valence electron configurations. These photocatalysts exhibit excited state lifetimes exceeding hundreds of nanoseconds. Simple 3d6 transition metal complexes containing abundant metals exhibit lifetimes below 1–2 nanoseconds, and they require multistep ligand syntheses mitigating large-scale implementation. We report that a commercially available bis(imidazolium) pyridine pro-ligand [H2pbmi]2+ and a manganese(II) salt yield the tetracarbene manganese(I) complex [Mn(pbmi)2]+. This complex phosphoresces at room temperature in fluid solution from a 3MLCT state with a lifetime of 190 ns. In combination with the reversible [Mn(pbmi)2]2+/+ process, this translates to an excited state capable of reducing benzophenone. Combination of manganese(I) with rigid carbene/pyridine ligands expands key strategies for photoactive 3d6 metal complexes of earth-abundant metals with 3MLCT lifetimes rivalling those of precious metals and providing a conceptual starting point for a sustainable photochemistry.